Using the Blockchain of Cryptocurrencies for Timestamping Digital Cultural Heritage - Gipp, Bela; Meuschke, Norman; Beel, Joeran; Breitinger, Corinna (My University, 2017)
The proportion of information that is exclusively available online is continuously increasing. Unlike physical print media, online news outlets, magazines, or blogs are not immune to retrospective modification. Even significant editing of text in online news sources can easily go unnoticed. This poses a challenge to the preservation of digital cultural heritage. It is nearly impossible for regular readers to verify whether the textual content they encounter online has at one point been modified from its initial state, and at what time or to what extent the text was modified to its current version. In this paper, we propose a web-based platform that allows users to submit the URL for any web content they wish to track for changes. The system automatically creates a trusted timestamp stored in the blockchain of the cryptocurrency Bitcoin for the hash of the HTML content available at the userspecified URL. By using trusted timestamping to secure a ‘snapshot’ of online information as it existed at a specific time, any subsequent changes made to the content can be identified.
Keywords: Web archiving; online news preservation; trusted timestamping; blockchain applications; 004